Evaluation and Forecast of Demand for Labor Force of the Agrarian Sector of Economy (Regional Aspect) - PARSHUKOV, Denis Victorovich; KHODOS, Dmitry Vasilevich; PYZHIKOVA, Natalia Ivanovna; VLASOVA, Elena Yuryevna (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The purpose of this study is to examine the problems of agricultural labor supply at the regional level. Methods of demographic forecasting and scenario and situation analysis were used to obtain the results. The relationship between labor productivity in agriculture, growth in agricultural production and the demand for labor in the medium term was studied. Object of the study was agricultural labor force of the Krasnoyarsk region. Forecasts of changes in the rural population and the working population of the region were made. The values of the labor force required to maintain the growth of production at the given parameters of productivity were defined. The basic solutions to the problems of lack of labor force were developed, based on the analysis of the current trends in the socio-economic development of regions. It was revealed that the likely option would be replacement of the local population deficit in the agricultural sector in the region by labor migrants from Central Asia.